Edible Offals Of Broiler That Given Turmeric Powder - I P. D. W., Setiawan; Astawa, I P. A.; Siti, N W. (Jurnal Peternakan Tropika; Vol 7 No 3 (2019): Issue 7 No. 3 - 2019; September - December 2019DO - 10.24843/ejpt.2019.v07.i03.p012, 2019)
The research aims to determine the effect to giving turmeric powder to edible offals broiler. This research was cobducted for 40 days with the starter phase of broiler chicken. The design used was a completely randomized design (CRD) with 3 treatments and 5 replications. The treatments given is P0 (without given turmeric powder in water), P1 (giving turmeric powder as much 0,5g/liter of water), and P2 (giving turmeric powder as much as 1g/liter of water). The variables observed were head percentage, claw percentage, liver percentage, heart percentage, rampage percentage, and percentage of small intestine. Data were analyzed by variance, if between treatments there were significant differences (P<0,05), then continued with Duncan’s multiple distance test. The results showed that administration of turmeric powder through water with 0,5g and 1g levels could increase cutting weight, but did not significantly (P>0,05) to head percentage, claw percentage, liver percentage, heart percentage, rampage percentage, and percentage of small intestine. Based on the results of the research, it can be concluded that administration of turmeric powder as much as 0,5g/ - 1g/1 liter though water not effect to broiler edible offals (percentage of head, claw, liver, heart, rampage, and small intestine). Keywords : Turmeric, Edible Offals, Broiler